Advanced, recurrent, and persistent cervical cancer management: in the era of immunotherapy - Galicia-Carmona, Tatiana; Arango-Bravo, Eder Alexandro; Coronel-Martínez, Jaime A.; Cetina-Pérez, Lucely; Vanoye-Carlo, Elva G.; Villalobos-Valencia, Ricardo; García-Pacheco, José A.; Cortés-Esteban, Patricia (Frontiers in Oncology, 2024)
Cervical cancer constitutes a significant health burden for women worldwide despite being preventable by vaccination and screening. Advanced stages of the disease are associated with a poor prognosis, and treatment approaches have seen little change over several decades, resulting in an overall survival rate of no more than 17 months. Additionally, there are limited options for second-line treatment. The urgent need for innovative and effective therapies to improve the outlook for this group of patients, along with an enhanced understanding of the interactions between the disease and the host’s immune system, has propelled immunotherapy into a rapidly advancing field with notable achievements. Among various immunotherapeutic approaches, immune checkpoint inhibitors emerge as the most advanced treatment option. Clinical trials assessing these inhibitors as single agents or in combination with chemotherapy show promising results. As immunotherapy begins to redefine standards of care for metastatic, recurrent, or persistent cervical cancer, this review addresses recent advances and current recommendations for its management in both first and second-line treatment. The goal is to provide insights into the evolving landscape of cervical cancer treatment, specifically focusing on immunotherapeutic interventions.